Long COVID in vaccinated women with Polycystic Ovary Syndrome: A retrospective cohort pilot study - Muharam, R; Bagastoro, Aswan; Faradina, Anindita Abigail; Yo, Edward Christopher; Irzanti, Alisha Nurdya; Sumapraja, Kanadi; Harzif, Achmad Kemal; Pratama, Gita; Maidarti, Mila; Silvana, Vita; Wiweko, Budi; Hestiantoro, Andon (Universitas Airlangga, 2025)
HIGHLIGHTS Among women with PCOS, many still reported persistent long COVID symptoms such as hair loss and fatigue. COVID-19 vaccination does not exacerbate symptoms of PCOS, which further emphasizes the importance of completing COVID-19 doses for women with PCOS to avoid long COVID sequelae. ABSTRACT Objective: Long COVID, or the persistence of symptoms after acute COVID-19 illness, can affect individuals with pre-existing health conditions such as polycystic ovary syndrome (PCOS). Long COVID and PCOS may share overlapping pathogenesis which potentially exacerbate one another. The aim of this study was to evaluate the symptoms of long COVID in women with PCOS who have been vaccinated and investigate whether COVID-19 vaccination or infection worsened PCOS symptoms. Materials and Methods: We carried out a retrospective cohort study on 44 women with PCOS who have been vaccinated and previously diagnosed with COVID-19. Questionnaires were distributed to find out the effect of COVID infection and vaccines in these women, as well as the symptoms of long COVID-19. Results: Of all participants, 28 women (70%) continued to report persistent long COVID symptoms, with the highest number of complaints being fatigue and hair loss. The results, using Mann-Whitney test, showed that there was no difference in PCOS symptoms before and after COVID-19 vaccination (p = 0.520) or after COVID-19 infections (p = 0.241). Although this study revealed a substantial prevalence of long COVID symptoms among women with PCOS, an encouraging finding emerged: neither the administration of COVID-19 vaccination nor prior infection with COVID-19 had a significant impact on PCOS-associated symptoms. Conclusion: This study further underscores the importance of vaccination for all individuals, including women with a history of PCOS. Furthermore, the purpose of COVID-19 vaccination is to mitigate symptom severity, thus potentially diminishing the occurrence of long-term COVID-19 symptoms in future cases.